收集探针及其使用方法 (2021)
提供了用于使用分子分析评价来自受试者的多个组织部位的组织样品的方法和装置。在某些方面，实施方案的装置允许收集液体组织样品和递送所述样品以用于质谱法分析。 Method and devices are provided for assessing tissue samples from a plurality of tissue sites in a subject using molecular analysis. In certain aspects, devices of the embodiments allow for the collection of liquid tissue samples and delivery of the samples for mass spectrometry analysis.